Assessing Superior Supply Chain Performance in the Tapioca Flour Agroindustry Using Scor and FSCN Models in Lampung Province - Intan Anisa Putri; Zainal Abidin; Ktut Murniati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
The problems that occur in the tapioca flour supply chain, in general, are the availability of raw materials that only rely on the season, which is known that the cassava harvesting process takes about 8 to 9 months, meaning that the average harvest is done once a year, in addition to the availability of raw materials that are difficult to relate to price fluctuations, so that if there is a problem of raw material supply shortages, it will hamper the production process which can cause delays in delivery so that it is not following the agreed contract, supply management, low yield rates and lack of distribution chain efficiency involving chain actors to consumers. This research aims to identify key elements in the tapioca starch supply chain, from farmers' suppliers to processing companies, and evaluate the performance of each element of the supply chain, which was conducted from August to December 2024. The data collection technique used was interviews with mapping of supply chain activities carried out through observation and Focus Group Discussion (FGD) methods. The study's respondents were 20, located in Lampung Province (Central Lampung and Pesawaran Districts). The research method used to analyze supply chain conditions using the Food Supply Chain Network (FSCN) with qualitative descriptive analysis identifies five supply chain components, including its structure, objectives, management, resources, and business processes, alongside performance analysis using Supply Chain Operation References (SCOR) with several attributes such as reliability, responsiveness, flexibility, and supply chain asset management. The novelty of this research is that it combines two analytical tools, namely FSCN and SCOR, to find out the detailed conditions of the company. The findings obtained after conducting the research are the condition and performance of each company in the superior category.